2020
DOI: 10.34105/j.kmel.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance of e-learning systems and the learning outcome of students at universities in Vietnam

Abstract: e-Learning systems nowadays become vital for many universities in developing countries. They are useful for increasing educational quality and providing students with high-quality learning resources. However, how to attract students to use e-learning systems and how to improve their learning outcomes through e-learning are still difficult questions. This paper presents a survey study with 357 students from universities in Vietnam. The analysis results showed that e-learning acceptance was influenced by five fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
0
22
0
3
Order By: Relevance
“…Ainsi, l'attitude du tuteur n'affecterait pas l'utilité perçue (Ibrahim et al, 2018;Y.-H. Lee et al, 2014). Dans le même sillage, les travaux de Q. T. Pham et Tran (2020) concluent que l'implication du tuteur n'avait pas d'effet sur l'acceptation, par les étudiants, des plateformes de formation à distance.…”
Section: Discussion : Quels Sont La Portée Et Le Positionnement Des Runclassified
See 1 more Smart Citation
“…Ainsi, l'attitude du tuteur n'affecterait pas l'utilité perçue (Ibrahim et al, 2018;Y.-H. Lee et al, 2014). Dans le même sillage, les travaux de Q. T. Pham et Tran (2020) concluent que l'implication du tuteur n'avait pas d'effet sur l'acceptation, par les étudiants, des plateformes de formation à distance.…”
Section: Discussion : Quels Sont La Portée Et Le Positionnement Des Runclassified
“…Pour ce qui a trait à la connectivité, nos résultats s'opposent également à ceux de Q. T. Pham et Tran (2020) qui ne trouvent aucun effet de la connectivité sur l'acceptation des plateformes de formation à distance. Nos résultats sont cependant en accord avec ceux de Y.-H. Lee et al (2014) qui établissent que l'accessibilité technologique influe positivement sur la facilité d'usage perçue.…”
Section: Discussion : Quels Sont La Portée Et Le Positionnement Des Runclassified
“…In this case, it is almost the only means to ensure access to quality education for a large number of young people. In particular, such conclusions were made based on the results of publications Asghar et al (2021), Pham and Tran (2020), Rupere and Jakovljevic (2021), and others.…”
Section: E-learning As a Means Of Meeting The Demand For Educational ...mentioning
confidence: 99%
“…LMS limited the evaluation on thinking and learning as the thinking style of the students not fully presented on online platform but it mostly measured the activity by selfassessment of the participants and analysis of log files (Lerche & Kiel, 2018). Pham and Tran (2020) encouraged the student to use e-learning system during learning program to increase the educational result because this study found that the more time of using e-learning system the better the learning outcome of students. This became the core factor that learning outcome of students is actually based on students' engagement in online learning.…”
Section: Problem Statementsmentioning
confidence: 99%